Pengaruh Penerapan E-Samsat Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Haryanto, Devin Anton; Lingga , Ita Salsalina (Jurnal Riset Akuntansi Politala, 2024)
Taxpayer compliance is the condition in which an individual complies with all applicable tax laws. Any individual who complies with the existing laws and fulfills their tax obligations can be considered compliant. With a high level of taxpayer compliance, the government's revenue increases, making it an interesting subject for research. The objective of this study is to explain the influence of e-SAMSAT implementation and tax penalties on taxpayer compliance. This research is quantitative in nature and utilizes purposive sampling as the sampling technique, with the condition that the vehicle taxpayers have used the e-SAMSAT application, resulting in 100 respondents from the Pajajaran tax office. Based on the data analysis results, it is found that e-SAMSAT implementation partially influences taxpayer compliance, while tax penalty variable does not have a partial influence on taxpayer compliance.